40.8k views
1 vote
(07.02)

An equation is shown below:

2(7x − 3) = 9

Which of the following correctly shows the beginning steps to solve this equation?

Step 1: 
14x − 3 = 
9
Step 2: 
14x = 
12

Step 1: 
14x − 6 = 
9
Step 2: 
14x = 
15

Step 1: 
9x − 3 = 
9
Step 2: 
9x = 
12

Step 1: 
7x − 1 = 
9
Step 2: 
7x = 
10

2 Answers

3 votes
2(7x − 3) = 9

First step you would do is distribute your 2 to your 7x and -3.
You would get: 14x-6=9
Second step: You would add 6 to both sides because you would want to get your 14 x to where then you'll be able to get x alone.
You would get: 14x=15 < That would be your answer
Answer: B

Now if you want to continue to solve:

Then you would divide each side by 14, because you'll want your x to be alone.
You would get: x=1.07.......

HOPE THIS HELPS! ^_^

User Alwin Kesler
by
6.2k points
2 votes
B. Step 1. 14x - 6 = 9
Step 2. 14x = 15
User StudioEvoque
by
5.5k points